UNSUR PEMBENTUK FILM PADA ANIMASI DORAEMON - Wibawa, I Komang Wira Satria; Deva, I Putu Satria Bhaskara; Amertha, I Dewa Agung Bagus Kresna Dhana; Nazih, Rifqi; Sugiartini, Ni Kadek (Pusat Penerbitan LPPM ISI Bali, 2023)
Doraemon is one of Japan's proudest animations. Awards for Doraemon include the Japanese Cartoonists Association award in 1973, the first Shogakukan Manga award for children's manga in 1982, and the first Samu Tezuka Culture award in 1997. This research analyzes the film-forming elements contained in the Doraemon animation. The research method uses observation and text analysis of Doraemon animation. The result of the analysis shows that Doraemon animation applies film forming elements. The elements are narrative elements and cinematic elements. The narrative elements include story, story structure, characters. While cinematic elements include: lighting, animation movement, editing and music.